Relationship Between Geriatric Patient Characteristics and Adherence to Outpatient Antihypertensive Therapy in Hospitals - Nisa, Fadlilatul Muthi’atun; Retnowati, Eko; Kurniawan, Galih (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study aimed to analyze the relationship between geriatric patient characteristics and adherence to antihypertensive therapy in the outpatient department of Sarkies ‘Aisyiyah Kudus Hospital, with the hypothesis that sociodemographic factors such as age, gender, education, occupation, socioeconomic status, duration of illness, and knowledge influence treatment adherence. Research Method: A quantitative analytical observational study with a cross-sectional approach was conducted from May to June 2025. The sample consisted of 60 geriatric hypertensive patients selected through purposive sampling. Data were collected using the validated MARS-5 questionnaire and a knowledge-level questionnaire. Data analysis included validity and reliability tests, as well as univariate and bivariate analyses using the Chi-Square test with SPSS 27. Results and Discussion: The majority of respondents (96.7%) demonstrated high adherence to antihypertensive therapy. Bivariate analysis revealed significant associations between education level (p = 0.039), occupation (p < 0.001), and knowledge level (p = 0.012) with adherence. In contrast, no significant relationships were found with gender, age, duration of hypertension, or socioeconomic status. These results suggest that knowledge, education, and daily activities significantly influence adherence behavior, whereas demographic characteristics alone do not. Implications: The findings underscore the importance of health education, family support, and pharmacist counseling in promoting adherence among geriatric patients, particularly those with limited knowledge or educational backgrounds. Future studies should involve larger populations, employ longitudinal designs, and investigate the role of family support and healthcare communication in enhancing long-term adherence.